Training on Using the Petanimilenial.id Financial Accounting Application to Improve Financial Accountability Among Millennial Farmers - Mustikawati , RR. Indah; Juliani, Dian; Sari, Ratna Candra; Priantinah, Denies; Taman, Abdullah (Journal of Islamic Economy and Community Engagement, 2025)
Digital transformation in the agricultural sector is an important requirement for achieving efficiency, transparency, and sustainability in farming businesses. However, low financial literacy and technological skills remain major obstacles for millennial farmers in managing their finances professionally. This community service activity aims to improve the financial accountability and digital capabilities of millennial farmers through training and assistance in using the Petanimilenial.id application. The program was implemented in Sleman Regency, Special Region of Yogyakarta, involving the millennial farmer community as partners. The implementation method included socialization, technical training, implementation assistance, and participatory evaluation using questionnaires. The results of the activity showed a significant increase in digital financial recording capabilities, understanding of application-based financial recording, and the preparation of simple financial reports. The overall average evaluation score of 4.27 (excellent category) indicates that the Petanimilenial.id application is considered easy to use, relevant to farming needs, and effective in improving financial accountability. The evaluation results show that this activity needs to be continued or further developed, with an average score of 4.73. In addition, this activity encourages an increase in farmers' confidence in making decisions based on financial data. This program proves that technology-based assistance can strengthen the financial literacy and professionalism of young farmers, while also being a concrete step towards sustainable agricultural digitalization in the modern economic era.